Cardio-pulmonary-resuscitation for people who use a wheelchair and/or have an atypical chest shape: an educational intervention. Issue 9 (24th April 2023) - Deegan, Elisha M.; Saunders, Annette; Wilson, Nathan J.; McCann, Damhnat
Abstract: Purpose: To determine the impact of the addition of information specific to people with atypical chest shapes and/or in a wheelchair during mandatory CPR classes on staff confidence to respond to emergency scenarios with these populations. Materials and methods: A pre-test post-test intervention study was conducted with staff from one of the largest disability organisations in Tasmania, Australia. Supplemented CPR and BLS classes were presented to participants. A purpose-designed questionnaire was completed pre, post, and six-months post after the training. Results: A significant rise in confidence post-training was demonstrated, and this was retained at the six-month time point. Time spent in the disability sector before the supplemented training or attendance at previous standard CPR classes did not have a significant effect on confidence levels before the supplemented training. Conclusions: Confidence is closely linked to willingness to act during emergency situations. Improved confidence may therefore result in improved willingness to act for people with disability, atypical chest shapes, and wheelchair users, thus improving health outcomes for these populations and providing this cohort with access to more equitable healthcare. IMPLICATIONS FOR REHABILITATION: Guidelines for undertaking CPR and BLS on people with atypical chest shapes and/or in a wheelchair are not currently available. Including information specific to people with atypical chest shapes and/or in a wheelchair during mandatory CPR classes increases staff confidence to respond to such situations. Supplementary disability-specific information can be successfully incorporated into existing CPR and BLS training.